2018
DOI: 10.3389/fimmu.2018.00448
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Analysis of the Human TCRγδ+ T-Cell Repertoire Reveals Shifts in Vγ- and Vδ-Usage in Memory Populations upon Aging

Abstract: Immunological aging remodels the immune system at several levels. This has been documented in particular for the T-cell receptor (TCR)αβ+ T-cell compartment, showing reduced naive T-cell outputs and an accumulation of terminally differentiated clonally expanding effector T-cells, leading to increased proneness to autoimmunity and cancer development at older age. Even though TCRαβ+ and TCRγδ+ T-cells follow similar paths of development involving V(D)J-recombination of TCR genes in the thymus, TCRγδ+ T-cells ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 64 publications
7
26
0
Order By: Relevance
“…This is in accordance with a recent study showing that gd T cells from adult peripheral blood present much lower TRG diversity than cord blood samples, a result of age-driven clonal expansion (15). Additionally, a skewed peripheral blood TRG distribution is observed in adulthood (15,40), indicating that the reduced diversity in the grafts might be related to expansion of TRG clones during life and harvested within the hematopoietic stem cells. Additional data are required to further show the reduced TRG diversity in grafts when compared with cord blood and adult samples.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with a recent study showing that gd T cells from adult peripheral blood present much lower TRG diversity than cord blood samples, a result of age-driven clonal expansion (15). Additionally, a skewed peripheral blood TRG distribution is observed in adulthood (15,40), indicating that the reduced diversity in the grafts might be related to expansion of TRG clones during life and harvested within the hematopoietic stem cells. Additional data are required to further show the reduced TRG diversity in grafts when compared with cord blood and adult samples.…”
Section: Discussionsupporting
confidence: 92%
“…Analyzing the CDR3 clonotypes revealed that postnatal thymocytes show a polyclonal repertoire (Fig. 2, C and D), as recently described (Kallemeijn et al, 2018; Di Lorenzo et al, 2019). In contrast, however, fetal γδ thymocytes displayed an oligoclonal repertoire (Fig.…”
Section: Resultssupporting
confidence: 78%
“…In contrast, human γδ thymocytes, at least postnatally, do not show such a functional commitment (Ribot et al, 2014). Further arguing against the generation of “innate” γδ T cells in the human thymus is the recent finding that the TRG and TRD repertoire of human pediatric thymuses and of term-delivery cord blood (CB) is highly polyclonal (Ravens et al, 2017; Davey et al, 2017; Kallemeijn et al, 2018; Silva-Santos and Strid, 2017; Di Lorenzo et al, 2017, 2019). In adults, the γδ TCR repertoire in the peripheral blood becomes less diverse and highly focused, highlighting the potential adaptive function of human γδ T cells (Ravens et al, 2017; Davey et al, 2017; Silva-Santos and Strid, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a shift towards more effector phenotypes, largely maintained TCR diversity and a change in Vγ/Vδ usage has also been detected in the peripheral blood of humans upon organismal ageing , suggesting similar age‐related processes occurring in the murine and human γδ T‐cell pool.…”
Section: Discussionmentioning
confidence: 86%